Mode-resolved detection of magnetization dynamics using x-ray diffractive ferromagnetic resonance - Burn, D; Zhang, S; Zhai, K; Chai, Y; Sun, Y; Van Der Laan, G; Hesjedal, T (American Chemical Society, 2019)
Collective spin excitations of ordered magnetic structures o er great potential for the development of novel spintronic devices. The present approach is to rely on micromagnetic models to explain the origins of dynamic modes observed by ferromagnetic resonance (FMR) studies, since experimental tools to directly reveal the origins of the complex dynamic behavior are lacking. Here we demonstrate a new approach which combines resonant magnetic x-ray diffraction with FMR, thereby allowing for a reconstruction of the real-space spin dynamics of the system. This new diffractive FMR (DFMR) technique builds on x-ray detected FMR (XFMR) that allows for element-selective dynamic studies, giving unique access to specific wave components of static and dynamic coupling in magnetic heterostructures. In combination with diffraction, FMR is elevated to the level of a modal spectroscopy technique, potentially opening new pathways for the development of spintronic devices.